1998
DOI: 10.1023/a:1007413018732
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Monitoring of oxygen uptake during general anesthesia would have several benefits, but unfortunately, this is usually not available in the clinical routine situation. The herein proposed formula to calculate oxygen uptake (.VO2) necessitates only the accurate measurement of FIO2 as well as fresh gas flow and composition. Additionally, this method is not affected by the presence of anesthetic gases. The calculation uses the difference in oxygen content between the delivered fresh gas and the resulting FIO2 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Despite that, Biro used a modified Foldes equation to calculate _ VO 2 during low flow anesthesia in a circle breathing system. 3 Biro's equation is simple, but does not correlate well with data obtained from patients and laboratory simulations. 10,12 We think that Foldes-Biro equation is an over-simplified description of a circle breathing system.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Despite that, Biro used a modified Foldes equation to calculate _ VO 2 during low flow anesthesia in a circle breathing system. 3 Biro's equation is simple, but does not correlate well with data obtained from patients and laboratory simulations. 10,12 We think that Foldes-Biro equation is an over-simplified description of a circle breathing system.…”
Section: Discussionmentioning
confidence: 93%
“…1,3,7 Foldes and colleagues recognized the difference between F I O 2 and F FG O 2 in a circle breathing system in 1956, 7 and presented an equation to describe the relation between F I O 2 , F FG O 2 , fresh gas flow, and…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the electronic fresh gas flowmeters seen on the latest types of anaesthesia delivery units would obviate the need for manual fresh gas flow data entry, such as we performed in our prototype system, and would allow full automation of the calibration routine. This method for the non-invasive measurement of V O 2 is similar in aim to that proposed by Biro (1998), which was based on a formula by Foldes et al (1952). Biro's method was tested in a clinical study against the reverse Fick method by Leonard et al who found poor agreement with a substantial negative bias in the order of 40-50% (Leonard et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Available techniques, by pulmonary artery catheterisation or indirect calorimetry, are either deemed too invasive or difficult to manage in a clinical study setting during non-cardiac surgery. Using oxygen uptake calculated from fractions of inspiratory and expiratory oxygen in the closed breathing circuit during low-flow anaesthesia [ 7 ] has not demonstrated agreement when compared to standard methods [ 8 ]. Importantly, it can not be used in awake patients in the postoperative period.…”
Section: Introductionmentioning
confidence: 99%